Bidirectional associations between eosinophils, basophils, and lymphocytes with atopic dermatitis: A multivariable Mendelian randomization study - Zeng-Yun-Ou, Zhang; Zhong-Yu, Jian; Wei, Li (Frontiers in Immunology, 2022)
Background Despite being prone to reverse causation and having unmeasured confounding factors, many clinical observational studies have highlighted the critical association between basophils, eosinophils, and lymphocytes and atopic dermatitis (AD). Whether these cells play a causal role in AD development remains uncertain. Methods Data were obtained from the UK Biobank and the Blood Cell Consortium, from a large publicly available genome-wide association study (GWAS) with more than 500,000 subjects of European ancestry and for AD from three independent cohorts with more than 700,000 subjects of European ancestry. We performed single-variable Mendelian randomization (SVMR), followed by multivariable Mendelian randomization (MVMR) to assess the total and direct effects of immune cell counts on AD risk. Results SVMR estimates showed that genetically predicted higher eosinophil [odds ratio (OR): 1.23, 95% confidence interval (CI): 1.17–1.29, p = 5.85E−16] and basophil counts (OR: 1.11, 95% CI: 1.03–1.19, p = 0.004) had an adverse effect on the risk of AD, while a higher lymphocyte count (OR: 0.93, 95% CI: 0.89–0.98, p = 0.006) decreased the risk. Reverse MR analysis showed higher basophil (beta: 0.04, 95% CI: 0.01–0.07, p = 0.014) and lower lymphocyte counts (beta: −0.05, 95% CI: −0.09 to −0.01, p = 0.021) in patients with AD. In MVMR, the effects of eosinophils (OR: 1.19, 95% CI: 1.09–1.29, p = 8.98E−05), basophils (OR: 1.19, 95% CI: 1.14–1.24, p = 3.72E−15), and lymphocytes (OR: 0.93, 95% CI: 0.89–0.98, p = 0.006) were still significant. Discussion Mendelian randomization (MR) findings suggest that an increase in the eosinophil and basophil counts and a decrease in the lymphocyte counts are potential causal risk factors for AD. These risk factors are independent of each other.